독거노인의 미충족 치과의료 관련요인: 2018년 지역사회건강조사 자료를 이용하여 - 김준하; Jun Ha Kim; 김소영; So Yeong Kim; 조경희; Kyung Hee Jo; 김예림; Ye Rim Kim; 최미진; Mijin Choi (대한구강보건학회지, 2021)
Objectives: The purpose of the study was to investigate the factors affecting unmet dental care needs among elderly living alone. Methods: The study subjects were 19,019 elderly living by themselves, who participated in the Korea Community Health Survey 2018 (KCHS, 2018). The data were analyzed using frequency analysis, Rao-Scott chi-square test, t-test, and binary logistic regression analysis, using the SAS 9.4 software. Results: Results from the multiple logistic regression analysis revealed a higher odds ratio (OR) for unmet dental care needs among those with a monthly household income below KRW 1,000,000 (OR=1.64, 95% confidence interval, 95%CI=1.39-1.92), compared to those with an income of above KRW 2,000,000. With regards to stress levels, unmet dental care needs were more prevalent among participants in the “stress moderate” (OR=1.19, 95% CI=1.06-1.33) and “stress” groups (OR=1.68 95% CI=1.48-1.92), compared to the “no stress” group. Furthermore, the OR for unmet dental care needs was significantly higher among participants in the “depression” group (OR=1.84, 95% CI=1.61-2.11) than the “no depression” group. Conclusions: Higher unmet dental care needs were found among participants in the low monthly household income, stress, and depression groups. Further study is needed to analyze the association between factors and needs related to unmet dental care.